Facile Synthesis of Single Iron Atoms over MoS2 Nanosheets via Spontaneous Reduction for Highly Efficient Selective Oxidation of Alcohols. Issue 19 (10th April 2022) - Li, Zhijun; Li, Honghong; Yang, Zening; Lu, Xiaowen; Ji, Siqi; Zhang, Mingyang; Horton, J. Hugh; Ding, Honghe; Xu, Qian; Zhu, Junfa; Yu, Jin
Abstract: The facile creation of high‐performance single‐atom catalysts (SACs) is intriguing in heterogeneous catalysis, especially on 2D transition‐metal dichalcogenides. An efficient spontaneous reduction approach to access atomically dispersed iron atoms supported over defect‐containing MoS2 nanosheets is herein reported. Advanced characterization methods demonstrate that the isolated iron atoms situate atop of molybdenum atoms and coordinate with three neighboring sulfur atoms. This Fe SAC delivers exceptional catalytic efficiency (1 atm O2 @ 120 °C) in the selective oxidation of benzyl alcohol to benzaldehyde, with 99% selectivity under almost 100% conversion. The turnover frequency is calculated to be as high as 2105 h −1 . Moreover, it shows admirable recyclability, storage stability, and substrate tolerance. Density functional theory calculations reveal that the high catalytic activity stems from the optimized electronic structure of single iron atoms over the MoS2 support. Abstract : Herein, a spontaneous reduction strategy to construct atomically dispersed Fe atoms over MoS2 is reported. The catalyst exhibits remarkable catalytic efficacy in the oxidation of benzyl alcohols. Density functional theory calculations reveal that the catalytic activity arises from the isolated Fe atoms over MoS2 and the energy barriers are quite moderate for the reaction.